Outsmarting Ebola through stronger national health systems - Obidimma Ezezika; Alpha Kabinet Keita (Scientific African, 2020)
The current outbreak occurring in the Congo highlights the continuous challenge that the continent of Africa faces with Ebola outbreaks. Since the first recorded Ebola outbreak occurred simultaneously in Democratic Republic of Congo (DRC) and in Sudan in 1976, there have been 27 recorded outbreaks in Africa by country with the most severe occurring in Guinea, Liberia and Sierra Leone in 2014. In this Letter to the Editor, we argue that the best way to outsmart such a pathogen in Africa is through investments in stronger national health systems. Keywords: Health system, Ebola, Infectious disease